FEATURES OF MICROCIRCULATORY PROCESSES IN GIRLS WITH DIFFERENT TYPES OF HAND MOTOR ASYMMETRY - Al-Shammari Mohammed J.I.; Masar Hadi Ismael; Shatha Khudaier Abbas; Pogrebnyak Tatyana A.; Khorolskaya Elena N.; Grigorenko Svetlana E. (European Science Publishing, 2024)
In a comparative aspect, the dynamics of microcirculation in the skin of the ring finger was studied according to the parameters of LDF-grams (Laser Doppler Flowmetry) (microcirculation in 17-19-year-old girls, taking into account the functional asymmetry of their hands under physiological conditions and under the influence of a thermal sample). The recording of the LDF-gram wave process, as a result of the superposition of microcirculation waves associated with their "active" and "passive" mechanisms in the frequency band from 0.0095 Hz to 1.6 Hz, has practical and diagnostic significance, both for scientific purposes aimed at evaluating various aspects of its reactivity and manifestation at different stages of human development. They are represented by non–overlapping frequency ranges (active – neurogenic, endothelial, myogenic) and two rhythms (passive - respiratory and cardiac) [ 2, 5]. Functionally, microcirculation processes determine the process of adequate response to shifts in the parameters of the external or internal environment. Our study was aimed at analyzing the nature of the relationship between the functional parameters of the cardiovascular system and the typological features of their nervous system of girls.
Keywords: microcirculation, LDF-gram frequency ranges.